Liberalism, constitutionalism, and democracy - Hardin, Russell (Oxford ; New York : Oxford University Press, 1999)
In his ground-breaking book, the leading political philosopher Russell Hardin develops a new theory of liberal constitutional democracy.
Includes bibliographical references and index.
Keywords: Democracy; Liberalism; Constitutional history -- United States